Race and Gender Bias in the Research Community on African Lions - Bauer, Hans; Gebresenbet, Fikirte; Kiki, Martial; Simpson, Lynne; Sillero-Zubiri, Claudio (Frontiers in Ecology and Evolution, 2019)
We used bibliometric data to show that Black, African and women researchers are underrepresented among authors of field studies on lions (Panthera leo) in Africa. This may lead to biased representation in institutions dealing with lion research and conservation and reinforce disenfranchisement with one of the most emblematic species in Africa. We discuss the causes, and ways for the lion research community to become more inclusive.